Effects of the control parameters on the stability of a laminar boundary layer on a porous flat plate - Lihonou, Toha François; Monwanou, Vincent A.; Miwadinou, Clément; Chabi Orou, Jean Bio (Zielona Góra: Uniwersytet Zielonogórski)
This work is devoted to the analysis of the linear temporal stability of a laminar dynamic boundary layer on a horizontal porous plane plate. The basic flow is assumed to be laminar and two-dimensional. The basic flow velocity profiles are obtained by numerically solving the Blasius equation using the Runge-Kutta method.
Keywords: permeability parameter; small Reynolds number; linear temporal stability; boundary layer; modified Orr-Sommerfeld equation; spectral collocation method